PERAN GERAKAN SOSIAL TRANSNASIONAL STOP ASIAN HATE DALAM ISU RASISME TERHADAP KETURUNAN ASIA DI AMERIKA SERIKAT 2021 - 2022 - Angel Denise Hutubessy, (2023)
This study aims to examine the role of Stop Asian Hate as a transnational social movement advocating racial equality among Asian minorities in the United States during 2021-2022. Utilizing the concepts of institutional racism and transnational social movements, a qualitative descriptive method with primary and secondary data sources was employed. Data collection was conducted through literature review, and data analysis followed four stages: data collection, data reduction, data presentation, and data presentation according to Miles & Huberman. The research uncovers manifestations of institutional racism at individual, intraorganizational, and institutional levels in the United States. The findings indicate that the Stop Asian Hate Movement has significantly contributed to promoting racial equality and has exerted pressure on policy makers in the country.